HULL INSPECTION PRODUCTIVITY MEASUREMENT FOR A NEW SHIPBUILDING PROJECT (CASE STUDY OF BIC 11.02 A NEW SHIPBUILDING PROJECT) - Endro W, Dimas (Department of Naval Architecture - Diponegoro University, 2013)
Hull construction process for a new shipbuilding project usualy consist of a set of stages. Starting from material identification, marking, cutting fabrication, assembly and testing. For many shipyard hull inspection activity and hull production stages are joined to simplify production progress monitoring. A 20% credit given for inspection activity. Inspection activities particulary for hull construction which consist of inspection and repair work. Schedule slip of a new shipbuilding is very potencial. This condition is met when man power allocation and work priority are not set properly. Therefore, a clear parameter which conduct with inspection productivity to production manager should be provided. This parameter could help production manager to determine priority of repair work. In this case, differences parameter between production that is using pane measurement and inspection that is using compartement measurement. These two different parameter could make difficulties, particulary when production manager want to know how much progess has been done. A new method to converting the two different parameter has become a topic of this paper